Subjecthood in Banjarnese - Alien Kurnia Warya Selia; Achmad Dicky Romadhan (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This research discusses the subject testing tools in the Banjar language. Subjecthood is one of the study materials within the scope of syntax. This research examines subject forms in the Banjar language using typological studies. Linguistic typology is one of the linguistic study theories and models founded on natural data and language structure systems. This research is descriptive qualitative research. This research data are clauses and sentences obtained in the direct speech of Banjar speakers. Respondents are Banjar individuals at least 18 years of age. They have a variety of genders, levels of education, native languages (L1), and places of residence. The study of the subjectivity of the Banjar language entails collecting data via multiple methods (observation and interview). The analysis method used in this research is the distributional method, followed by the advanced method. The result of this research states that the subjugation of the Banjar language follows the typology theory of subject testing. There are five types of subject testing tools applied in this research: canonical structure, relativization, control, adverbial insertion and reflexive. The use of typology theory can reveal the subject test tools.